1982
DOI: 10.2134/agronj1982.00021962007400040022x
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Germplasm and Cultivar Aluminum Tolerance in Nutrient Solution and Bladen Clay Loam Soil1

Abstract: High Al in acid subsoils of the Southeastern States often restricts root growth and moisture utilization. Liming subsoil is difficult and expensive. An alternative or substantial approach is to select or breed plant genotypes having greater tolerance to Al. The differential Al tolerances of soybean [ Glycine max(L.) Merr.] representing Maturity Groups V, VI, and VII were determined in a growth chamber using nutrient solutions containing 0 and 8 ppm Al. Screening was also done on acid (4.2) and limed (5.8) in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
5

Year Published

1984
1984
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 4 publications
1
11
0
5
Order By: Relevance
“…No entanto, a expressão de classes de tolerância foi melhor caracterizada na avaliação do nono dia: a FT-1 como a mais tolerante, seguida da Andrews. Entretanto, alguns autores conseguiram boa separação na tolerância ao Al entre os genótipos de soja no quinto dia (Hanson & Kamprath, 1979), no sexto dia (Sapra et al, 1982) e, no sétimo dia (Mascarenhas et al, 1984a), em virtude da utilização de diferentes soluções, parâmetros de avaliação e tipo de controle dos fatores ambientais.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…No entanto, a expressão de classes de tolerância foi melhor caracterizada na avaliação do nono dia: a FT-1 como a mais tolerante, seguida da Andrews. Entretanto, alguns autores conseguiram boa separação na tolerância ao Al entre os genótipos de soja no quinto dia (Hanson & Kamprath, 1979), no sexto dia (Sapra et al, 1982) e, no sétimo dia (Mascarenhas et al, 1984a), em virtude da utilização de diferentes soluções, parâmetros de avaliação e tipo de controle dos fatores ambientais.…”
Section: Resultsunclassified
“…A vantagem é permitir a observação dos efeitos do Al sobre as raízes em fases iniciais, sem que seja interrompido o desenvolvimento das plantas (Moore et al, 1976). Considerando que o efeito primário do Al é sobre as raízes, com inibição da divisão celular, o parâmetro mais utilizado é o do desenvolvimento das raízes, com ênfase no comprimento da raiz principal (Hanson & Kamprath, 1979;Sapra et al, 1982;Mascarenhas et al, 1984aMascarenhas et al, , 1984b.…”
Section: Tolerance Of Soybean Genotypes To Aluminum In Solutionunclassified
See 1 more Smart Citation
“…Recent research on peanut indicated that root characteristics of plants grown in hydroponics were closely related with those of plants grown with soil in small pot conditions (Girdthai et al 2010). Hydroponic evaluation identified the soybean cultivar Perry as Al sensitive even though it had been found to be tolerant in soil-based assays with older plants (Armiger et al 1968;Foy et al 1969Foy et al , 1992Devine et al 1979;Sapra et al 1982;Horst and Klotz 1990). VAX1 which was found to be Al sensitive in hydroponic system was found to be acid soil tolerant under field conditions because of its abundant adventitious root system that helped avoid Al toxicity.…”
Section: Root Traits Across Experimentsmentioning
confidence: 99%
“…A seleção de material tolerante e suscetível ao Al 3+ tem sido feita por vários autores, utilizando solução nutritiva com níveis tóxicos deste elemento (7,8). Foi demonstrado por MASCARENHAS & CAMAR-GO (4) que o comprimento da raiz primária foi um parâmetro adequado para a identificação e seleção de cultivares de soja quanto à toxicidade de Al 3+ em solução nutritiva.…”
Section: Introductionunclassified